Recent developments in labor economics - Addison, John T. (Cheltenham, UK ; Northampton, MA : Edward Elgar, 2007)
A comprehensive set of papers that charts the main developments in contemporary labour economics, with an emphasis on issues of measurement.
"An Elgar reference collection".
Includes bibliographical references and index.
oif 31/08/15
Loan
Keywords: Labor economics